Icaritin improves pregnancy outcomes in endometriosis by inhibiting ovarian granulosa cell senescence - Yalun He; Jie Ding; Yangshuo Li; Ji Sun; Cuiping Wei; Na Sun; Runnan Jiang; Ziming Zhao; Xiaolan Liang; Yiming Chen; Wen Cheng; Litai Zhang; et al. (Molecular Biology Reports, 2026)

XsiAMT1.1a was identified as a novel ammonium uptake functional gene and its overexpression combined with GA4 application significantly increased yield in Arabidopsis thaliana - Xiao Han; Zhao-Hua Gong; Jie Cao; Li-Na Ye; Yuan Cheng; Yu-Xuan Du; Ting-Ting Zhao; Hai-Long Wu; Chang Zhang (Plant Science, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

The dynamic complexity of critical mineral supply chains reveals the paradox of energy transition - Junhui Li; Yongguang Zhu; Shiquan Dou; Qian Zhang; Saleem H. Ali; Gang Liu; Yanqiong Zhao; Na Zhou; Jinhua Cheng; Deyi Xu (Ecological Economics, 2026)

High-pressure CO₂ spraying of electret melt-blown polypropylene for piezoelectric self-sensing respiratory monitoring masks - Jiahui Xu; Xiaoyue Zou; Ning Cao; Yunchen Yao; Yuxin Jia; Na Zheng; Zhenshu Chen; Youqiang Yang; Zhanquan Lu; Xiangrong Chen; Pengfei Xie; Cheng Li; et al. (Chemical Engineering Journal, 2026)

Cadmium stress restructures bacterial communities but induces limited variation in predicted functional profiles in the rhizosphere of Sedum plumbizincicola: implications for Cd phytoremediation - Yanan Cheng; Jing Jiang; Shangqi Xu; Meng Na; Xiaoping Li; Jihai Zhou (Rhizosphere, 2026)

Annual energy use and economic performance of rice-based cropping systems: A three-year field study in Southwest China - Chuanhai Shu; Qingyue Cheng; Binbin Liu; Hongkun Xie; Yuanqing Shi; Mingming Hu; Hao Fu; Peng Ma; Na Li; Zhonglin Wang; Zongkui Chen; Yongjian Sun; et al. (Journal of Cleaner Production, 2026)

Exopolysaccharides from Enterococcus faecium alleviate cadmium damage in rice seedlings via regulating soil-root nitrogen metabolism - Min Zhong; Min Li; Chun-na Zhong; Zu-xuan Yan; Wei-fu Peng; Xin Cheng (Journal of Environmental Sciences, 2026)

Mango peel pectin as a high-ester emulsifier for carotenoid delivery: Structural characterization and application in low-fat ice cream - Teng-Gen Hu; Huan Zhang; Lu Li; Yu-Qing Hu; Jing Wen; Bo Zou; Jian Peng; Li-Na Cheng; Ji-Jun Wu; Geng-Sheng Xiao; Yu-Juan Xu; Yuan-Shan Yu (Carbohydrate Polymers, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Association of single and combined metal burdens with systemic immune inflammation in smelter workers: A population-based study - Di Wu; Yuankai Cheng; Shuxian Wang; Na Wang; Danhua Zhang; Zhaoyan Wang; Jianxia Cao; Yuzheng Li; Yanhong Li; Jinrui Ma; Yingzheng Zhao; Sihua Wang (Journal of Trace Elements in Medicine and Biology, 2026)

Identifying driving factors of lacustrine groundwater discharge in Lake Taihu with integrated surface-subsurface numerical modeling - Hao Zhou; Yadong Shi; Yue Zou; Ya Jiang; Na Zheng; Subin Cheng; Donghao Wu; Xin Luo; Chaomeng Dai; Juntao Zheng; Zhi Li (Journal of Hydrology, 2026)

The abiotic drivers of soil system perturbation by metallic nanomaterials: a critical review bridging interfacial processes to environmental risks - Mengcheng Zhang; Xue Li; Yongchao Zhao; De'an Chen; Na Tian; Wenrui Zhang; Dongle Cheng; Guang Yang; Xiaoqiang Cao; Yanlong Wang; Huaqing Liu; Jian Zhang (Environmental Research, 2026)

Microglial Alkbh5 Deficiency Alleviates Chronic Restraint Stress-Induced Depression-like Behaviors in Mice - Ao Li; Lu Han; Jia Guo; Na Zhang; Ranxu Liu; Jingdan Zhang; Xiaoheng Li; Zengqiang Yuan; Jinbo Cheng (Neuroscience Bulletin, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Straw mulching combined with alternate wetting and drying reduces methane emissions in paddy fields: associations with carbon availability and methanogenic archaeal community shifts - Chuanhai Shu; Zhonglin Wang; Binbin Liu; Yue Huang; Yuanqing Shi; Hongkun Xie; Mingming Hu; Qingyue Cheng; Qin Liao; Na Li; Zongkui Chen; Yongjian Sun; et al. (Journal of Environmental Management, 2026)

Corrigendum to “Effects of quinoa addition on physicochemical properties, microbiome profiles, and volatile organic compounds in medium-temperature Daqu” [Food Res. Int. 223 (2026) 117868] - Wei Cheng; Chao Jiang; Tianquan Pan; Qingyun Zhu; Gengdian Liu; Na Li; Zaijie Wu; Xingjiang Li (Food Research International, 2026)

An active cling film developed from pomelo peel for synergistic preservation of Oncorhynchus mykiss: Utilizing K/Fe enzyme-like materials and natural extracts - Tao Yu; Long Cheng; Yini Zhao; Long Gu; Hangfei Gao; Zicen Liu; Li Huang; Shuyan Bai; Dongli Qin; Peng Wang; Aimin Wang; Haijiao Xie; et al. (Food Packaging and Shelf Life, 2026)

Protective effects of melatonin on mouse ovarian tissue against oxidative stress and ferroptosis may involve the MT1 receptor - Sheng Nan Jiang; Xin Zhang; Li Na Si; Meng Wei; Xin Hui Wei; Yong Wei Wang; Tie Cheng Sun; Song He Yang; Zhi Hong Chen; Lu Yang Cheng (Cryobiology, 2026)

Nanostructured electrospun nitrocellulose: Stabilization mechanisms and degradation kinetics of organic stabilizers - Wen-Jie Xu; Xue-Ning Cheng; Zhong-Xuan Han; Zhan-Jun Yang; Shu-Na Zhao; Hao Liu; Mi Li; Lin Jiang (Fuel, 2026)

Geographic discrimination of Sauce-flavor rounded-base Baijiu using GC–MS/MS combined with multivariate analysis and machine learning - Sen Luo; Yi Shen; Wei Cheng; Na Wang; Yadong Zhang; Jian Wang; Di Chang; Juxiu Li; Xinguang Guo; Hongbo Gao (Food Chemistry, 2026)

Exploration of chicken lung antioxidant peptides modified by plastein reaction: Purification, identification and molecular docking - Jingwen Jia; Siyu Cheng; Lisheng Li; Tian Chen; Na Xu; Xiaomei Sun; Yun Bai; Xinglian Xu; Minyi Han (Food Bioscience, 2026)

Atrazine increases hepatic inflammation and injury via endoplasmic reticulum (ER) stress mediated excessive formation of mitochondria-associated membranes (MAMs) and activation of the cGAS-STING pathway - Zi-Jun Sun; Guan-Yue Shan; Hui Wan; Yu-Xin Zhang; Zhi-Cheng Gao; Wen-Na Shi; Lei Lv; Wei-Qun Yan; Hai-Jun Li (Environmental Pollution, 2026)

Organic fertilization alleviates soil sickness in monoculture systems by driving pathogen-suppressive rhizosphere community assembly - Tong Peng; Chuanji Zhang; Xiaoqi He; Zhenyu Cheng; Junjie Li; Yanfang Song; Ziyu Liu; Meiyun Pu; Yi Yan; Panshuai Fei; Yurong Bi; Xiaofan Na (Plant and Soil, 2026)

Spatiotemporal distribution and host association of antibiotic resistance genes in sediment of Qiantang river basin - Qiannan Jin; Jie Li; Yantan Zhou; Guangqian Zhao; Yuhan Jiang; Na Cheng; Lifang Hu (Environmental Geochemistry and Health, 2026)

Effects of cadmium-tolerant bacteria combined with biochar on cadmium and selenium dynamics in rice grown on seleniferous soils: Insights from a soil bacterial community analysis - Yanan Cheng; Jing Jiang; Lanping Song; Shangqi Xu; Meng Na; Kun Cheng; Daming Li; Shoubiao Zhou; Jihai Zhou (Journal of Environmental Chemical Engineering, 2026)

Analysis and regulation of baijiu aroma-active compounds: integrating metabolomics, sensory genomics, and artificial intelligence - Wei Cheng; Na Li; Tianquan Pan; Qingyun Zhu; Wei Lan; Gengdian Liu; Yuxi Guo; Xuefeng Chen (Food Research International, 2026)

Spatio-temporal distribution, ecological risks and possible sources of heavy metals in Lake Gahai on northeastern Qinghai-Tibet Plateau: Response to anthropogenic activities and environmental changes - Jinxin Wen; Chunliang Gao; Aiying Cheng; Haicheng Wei; Xiuyun Min; Hongyu Li; Chenyu Wang; Na Chao; Bo Dong (Anthropocene, 2026)

Screening of quorum Sensing-Dependent strong promoters in Pseudomonas bijieensis 2P24 for metabolic optimization and Recombinant protein production - Jie Li; Hongguang Ma; Na Tai; Yue Fan; Mengxue Nie; Xuanying Tao; Zhilin Wang; Jinxin Wang; Xiangpeng Deng; Cheng Shen; Xuanxuan Chen; Jin Wang; et al. (World Journal of Microbiology and Biotechnology, 2026)

Nigrospora aurantiaca causes leaf spot disease in Bletilla striata in China - Na Wu; Zhen Su; Junyi Gao; Dengquan Liu; Maoxian Wang; Zhongshun Cai; Cheng Li (Crop Protection, 2026)

An enhanced cow-teat-detection model for automatic teat-cup-attachment devices - Mengjie Li; Juan Wang; Na Li; Yaju Liu; Xue Cheng; Xinpei Fu; Sirui Li (Biosystems Engineering, 2026)

Conventional low-density polyethylene microplastic induce stronger adverse effects on maize–soil–bacteria system than polylactic acid microplastic - Yixiu Wang; Hongyan Cheng; Chaodong Yang; Yonghui Lv; Yi Wang; Yuenan Li; Haibo Zhang; Na Liu (Journal of Environmental Management, 2026)

Research on pore structure and fractal characteristics of low-medium rank coals before and after acidification with H2S aqueous solution based on NMRC - Yan Wang; Haichao Wang; Xin Li; Chao Jia; Xiaoqian Cheng; Na Zhang; Bo Wang; Peng Lai; Zhenpeng Hu; Zhengkai Liao (Fuel, 2026)

Unveiling the genetic architecture of stripe rust resistance in wheat: a region-specific GWAS in Xinjiang, China - Feifei Zhang; Rong Wang; Wenjuan Jiao; Wanlong He; Yuzhe Zhang; Na Sun; Bin Bai; Kemei Li; Yukun Cheng; Hongwei Geng (Theoretical and Applied Genetics, 2026)

Identification of low-toxicity DNA topoisomerase I inhibitors with potential blood–brain barrier penetrability for glioblastoma therapy: structure-based virtual screening reveals promising novel Scaffolds - Ya-Lin Li; Jun Mao; Zhong Cheng; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

Application of an innovative BMask R-CNN-DAT enhanced with feature extraction and boundary awareness in tunnel leakage detection - Yu Li; Huai-Na Wu; Hong-Zhan Cheng; De-Sai Guo; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Comprehensive analysis of metabolic response in Arabidopsis thaliana under heavy metal stress by mass spectrometry - Zhongyan Zhou; Donghao Li; Na Wang; Xiujuan Hong; Wen Su; Cheng Guo; Chongsheng He; Lei Yue (Journal of Hazardous Materials, 2026)

Effects of quinoa addition on physicochemical properties, microbiome profiles, and volatile organic compounds in medium-temperature Daqu - Wei Cheng; Chao Jiang; Tianquan Pan; Qingyun Zhu; Gengdian Liu; Na Li; Zaijie Wu; Xingjiang Li (Food Research International, 2026)

An update review on plasma-driven polysaccharide degradation: Effects on physicochemical properties, structural characteristics and biological activities - Zhoujie Xu; Xinyao Li; Wen Li; Na Cheng; Kai Li; Zhi Huang (Food Chemistry, 2026)

Comprehensive assessment of secondary metabolite diversity and in vitro anti-diabetic properties in Sanghuangporus quercicola cultured under different conditions - Mingxing Yu; Na Zhang; Xiaofeng Ma; Xiaoshuang Zhou; Shude Yang; Weihang Peng; Yin Li; Yuejun Mu; Xianhao Cheng; Rui Zhang; Yongfei Ming (Systems Microbiology and Biomanufacturing, 2026)

Novel interface-enhanced bimetallic nanozyme-mediated magnetic integrated nanoplatform for integrated prevention and control of pathogenic bacteria - Xiaoyu Yu; Xin Zhang; Yuwei Ren; Rui Jiao; Hui Li; Mengyu Li; Weichao Wu; Na Ling; Danfeng Zhang; Jianghua Cheng; Yingwang Ye (Analytica Chimica Acta, 2026)

Structure-based molecular design of fungicidal β-ketonitrile derivatives with biphenyl moiety as novel succinate dehydrogenase inhibitors - Cong Zhou; Ziye Cao; Li Sun; Na Zhai; Liangliang Cheng; Zheyi Feng; Zhong Li; Xuhong Qian; Jiagao Cheng (Pesticide Biochemistry and Physiology, 2025)

Anti-diabetic effects of probiotic and postbiotic Lactiplantibacillus plantarum R6-3 from Sayram ketteki in T2DM mice via modulating gut microbiota and intestinal barrier - Yajing Liu; Chen Li; Bingyong Mao; Na Zhang; Chenwei Li; Fenghe Qin; Shumei Cheng; Qinghai Sheng; Miaoshu Wang; Dongyao Li; Hongtao Tian (Food Bioscience, 2025)

New uses for old drugs: Targeted paroxetine-loaded liposomes for effective inhibition of cardiac fibrosis - Yang An; Ge Sun; Zhenzhen Dong; Yang Liu; Yubiao Huang; Xiaoyu Cheng; Wentao Zheng; Jiarui Du; Na Li; Yinlong Zhang; Chengzhi Yang (Chemical Engineering Journal, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Comparison of Lycium barbarum and Chenopodium glaucum litter decomposition reveals differential impacts on fusarium abundance and microbial community structure under field conditions - Chuanji Zhang; Zhenyu Cheng; Xiaoqi He; Meiyun Pu; Junjie Li; Ziyu Liu; Xiaomin Wang; Yurong Bi; Liguang Wang; Xiaofan Na (Applied Soil Ecology, 2025)

Unveiling regulatory network of porcine oocyte IVM using integrated multi-omics - Yufen Jiang; Helin Li; Na Cheng; Yuchen Han; Qiue Xu; Mingjin Li; Muhammad Ameen Jamal; Jianxiong Guo; Honghui Li; Hong-Jiang Wei; Wenmin Cheng (Livestock Science, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Occurrence and fugacity model simulation of organophosphate esters in atmosphere-soil-vegetation, Fildes peninsula, Antarctica - Guanjie Cheng; Ruijing Li; Yunfeng Xu; Chao Hou; Xuan Jia; Bing Li; Hui Gao; Shuaichen Jin; Liang Kong; Guangshui Na (Journal of Environmental Sciences, 2025)

Closing in on carbonate uranium isotopes as a paleo-redox proxy based on continuous records from Late Oligocene to Holocene island carbonates - Guolin Xiong; Feifei Zhang; Yi-Bo Lin; Guang-Yi Wei; Na Li; Mengchun Cao; Xuexue Jia; Jian Wang; Wen Yan; Hai Cheng; Shu-zhong Shen (Geochimica et Cosmochimica Acta, 2025)

Carbonate-intercalated aluminum layered double hydroxide for high-capacity lithium extraction - Lei Zhang; Yuanyuan Li; Xiaohan Qiao; Ruona Li; Tuo Li; Penggao Cheng; Jianping Zhang; Na Tang (Desalination, 2025)

Effects of selenium–cadmium interactions on soil cadmium forms and the enrichment of selenium and cadmium in rice - Tianyi Lu; Yong He; Yanmei Ai; Meng Na; Shangqi Xu; Kun Cheng; Daming Li; Jihai Zhou (Plant and Soil, 2025)

Returning low C/N crop straw to the paddy field can achieve the dual benefits of reduced methane emissions and enhanced yield stability - Chuanhai Shu; Binbin Liu; Yu Li; Qiqi Chen; Leilei Li; Yuanqing Shi; Hongkun Xie; Zhonglin Wang; Qin Liao; Qingyue Cheng; Feijie Li; Na Li; et al. (Agriculture, Ecosystems & Environment, 2025)

Intrinsic electron transfer kinetics of electroactive granular sludge bioanode boosting bio-electro-Fenton efficiency - Bao-Gang Fu; Shu-Na Li; Xiangtong Zhou; Xiang Xiao; Liang Cheng; Yang-Yang Yu (Journal of Environmental Chemical Engineering, 2025)

Microplastics and human health: Exposure pathways, toxicity mechanisms, and future research challenges - Zhi Wang; Nuo Li; Yongcheng Ding; Na Li; Menghan Su; Congcong Zhang; Yiqun Li; Qing Wang; Chenyan Sha; Bing Xia; Jie Cheng; Guan Jiang (Journal of Environmental Chemical Engineering, 2025)

Insights into the multiple nitrogen removal mechanisms of anammox consortia induced by iron scraps - Shuyan Yin; Yi-Xuan Wang; Muyu Li; Na Li; Cheng Hou; Xinbai Jiang; Jinyou Shen (Chemical Engineering Journal, 2025)

A new phenolic amide and other components from the scapes of Gastrodia elata and their chemotaxonomy significance - Na Li; Jing-Jing Zhang; Chan Chen; Yun-Na Wang; Xiao-Li Li; Li-Jun Cheng; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Ni nanoparticles inlaid in amorphous silicon nitride-derived nickel phyllosilicate: A highly stable and active catalyst for ammonia decomposition - Han Yang; Jing Li; Qiang Chang; Qun-chao Zhao; Meng-na Zhang; Huan-jiang Wang; Cheng-hua Zhang; Fei Wang; Xiao-dong Wen (Fuel, 2025)

Contrasting fungal community assembly mechanisms in bulk soil and rhizosphere of Torreya grandis across a 900-year age gradient - Bin Wang; Xiaofan Na; Shengyi Huang; Zhengcai Li; Zhichun Zhou; Juying Huang; Meiyun Pu; Zhenyu Cheng; Xiaoqi He (Plant and Soil, 2025)

A portable point-of-care testing platform for rapid and sensitive miRNA-21 detection for heart failure diagnosis - Qian Kai Lin; Wen Qing Sun; Bo Zhang; Qiao Ling; Yan Qian; Cheng Zhi Huang; Chun Mei Li; Na Wang (Analytica Chimica Acta, 2025)

Mass and heat balance of sea ice during the thaw-freezing transition in the Pacific sector of Arctic Ocean derived from the buoy measurements in 2018 - Mengqi Wu; Ruibo Lei; Bin Cheng; Long Lin; Na Li; Xiaomin Chang (Acta Oceanologica Sinica, 2025)

Mitigating the impacts of ionospheric irregularities on GPS precise positioning by refined cycle slip threshold - Wei Li; Shuli Song; Tianyang Bai; Na Cheng; Weili Zhou; Chao Yu (GPS Solutions, 2025)

UV-B stress reshapes root-associated microbial communities and networks, driven by host plant resistance - Chuanji Zhang; Na Gao; Xiaofan Na; Kaile Li; Meiyun Pu; Hao Sun; Yanfang Song; Tong Peng; Panshuai Fei; Junjie Li; Zhenyu Cheng; Xiaoqi He; et al. (Soil Biology and Biochemistry, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

Short-term PS-NP exposure in early adulthood induces neuronal damage in middle-aged mice via microglia-mediated neuroinflammation - Shan Shan; Dong Cheng; Hui Li; Wenhuan Yao; Ruirui Kou; Jing Ji; Na Liu; Tao Zeng; Xiulan Zhao (Journal of Hazardous Materials, 2025)

Fate of myofibrillar protein-bound Nε-(carboxymethyl)lysine in the presence of the human colonic microbiota after gastrointestinal digestion - Shuqi Hao; Zeyu Lu; Mengyu Ye; Na Li; Jiayi Hu; Wei Quan; Jiwen Cheng; Huaide Xu; Mei Li (Food Bioscience, 2025)

Structure identification and biological activity of a novel sulfated glycosaminoglycan-like polysaccharide from Sepia recurvirostra ink - Nanqi Cheng; Na Gao; Pin Wang; Yujun Ma; Pengfei Li; Xiaolu Wu; Jiaying Sun; Yulan Dai; Jinhua Zhao (Carbohydrate Polymers, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Deformation and protection of tunnels influenced by excavation dewatering in soft soil strata with leaky aquifers - Qinghan Li; Gang Zheng; Xuesong Cheng; Xiaorui Shi; Na Zhang; Shilong Zhou; Wenlong Cheng (Tunnelling and Underground Space Technology, 2025)

Prevalence of hypervirulent Klebsiella pneumoniae and application of the novel Klebsiella phage vB_KpnP_D39 for biocontrol of serotypes K1, K2, and K57 in prepared food-related samples - Diwei Zhang; Rui Jiao; Bin Cheng; Xiyan Zhang; Hanfang Chen; Hui Li; Xiangyu Cheng; Na Ling; Yingwang Ye (International Journal of Food Microbiology, 2025)

Molecularly imprinted polymer combined with multiple-component covalent organic frameworks for extraction of naringenin enantiomers - Juanqiong Ma; Na Yang; Xingyuan Zhang; Manyi Xiao; Cheng Cao; Zhiyong Xie; Pei Li; Qiongfeng Liao; Yanlong Chen (Food Chemistry, 2025)

Structural and electronic regulation of transition metal borides: from controllable synthesis to industrial alkaline water splitting - Na Xu; Xin-Ru Li; Denghao Ouyang; Guodong Li; Shijian Cheng; Zhongmin Tang; Yong-Ming Chai; Bin Dong (Fuel, 2025)

Magnetic graphene-enhanced exonuclease III assisted amplification strategy driven carbon nanozyme for tri-mode detection of Escherichia coli O157:H7 - Yuwei Ren; Lulu Cao; Zongyang Li; Xin Zhang; Hui Li; Rui Jiao; Xiaoyu Yu; Zhao Liang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; et al. (Food Chemistry, 2025)

Immunofluorescent analysis of exosomes using a microchip filled with transparent antibody-conjugated beads for breast cancer liquid biopsy - Na Li; Cheng Cheng; Di Wu; Zixuan Song; Bei Wang; Guiying Li; Fang Yang (Analytica Chimica Acta, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

GmHSP40.1, a nuclear-localized soybean J domain protein, participates in regulation of flowering time through interacting with EMF1 and JMJ14 - Chi Zhang; Hu-Jiao Lan; Li-Na Liao; Min-Jun Huang; Wei Xu; Hui Zhang; Qianqian Ma; Feng Li; Ninghui Cheng; Paul A. Nakata; Steven A. Whitham; Jian-Zhong Liu (Plant Science, 2025)

Sesquiterpenoids from Inula britannica and their potential mechanism for immunomodulation - Hui-Lin Zhang; Na Wang; Xu-Liu Shi; Miao-Miao Wang; Qi-Meng Zhu; Jing Chang; Yan-Li Feng; Juan Zhang; Feng Qiu; Cheng-Peng Sun (Phytochemistry, 2025)

Characterization of microplastic distribution, sources and potential ecological risk assessment of domestic sewage from ships - Na Lu; Qing Su; Yuxia Li; Ling Qu; Lingna Kong; Jiayi Cheng; Chao Wang; Jian Sun; Jianbo Han; Xiaomeng Wang (Environmental Research, 2025)

Association between maternal serum zinc and birth weight is modified by neonatal SOD2 polymorphism and promoter methylation - Yuting Zeng; Yalong Wang; Yanan He; Qinyang Li; Ruiqin Chen; Cuiping Wu; Na Li; Xinya Cheng; Yuhui Du; Fangfang Yu; Yue Ba; Guoyu Zhou (Journal of Trace Elements in Medicine and Biology, 2025)

Green preparation of low-molecular-weight galactomannan from Gleditsia sinensis and mechanistic investigation on ameliorating nonalcoholic fatty liver disease - Chi Feng; Xichuang Cheng; Mula Na; Fenglun Zhang; Jiufang Duan; Li Ji; Jianxin Jiang (Food Research International, 2025)

Evaluation of water environmental capacity in a northern river-reservoir continuum using environmental fluid dynamics code - Qingqing Sun; Huanlian Ren; Mohd Aadil Bhat; Na Liu; Zhaolun Li; Zechao Li; Qiliang Cheng; Yimeng Ren; Ning Yang; Zhuoni Ma (Science of The Total Environment, 2025)

A Se-hyperaccumulating plant Cardamine violifolia: From its nutritional value to potential applications in foods - Li Wang; Shuyi Li; Feifei Wang; Na Zhang; Xu Chen; Xuehua Wang; Jiangling He; Chen Cheng; Zhenzhou Zhu (Trends in Food Science & Technology, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Durable underwater superoleophobic hydrogels for oil- and Cu(II)-containing water purification - Chang-Lian Xu; Na Ji; Xingyue Wu; Xiaoxun Xu; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Shirong Zhang; Ting Li; Pietro Paolo de Oliveira e Silva; Guochun Lv; Junzhuo Cai; et al. (Journal of Environmental Chemical Engineering, 2024)

Exogenous melatonin improves peanut field productivity and quality at reduced nitrogen application - Lijie Li; Xiangguo Cheng; Yi Zhang; Dana Kohtz; Xiaohui Wang; Xiaotian Zhang; Xiangjun Kong; Huiyun Xue; Peipei Jia; Na Bai; Zengqiang Li; Peng Xiao; et al. (Field Crops Research, 2024)

Ru induced charge redistribution of MnO2 spheric nanozyme boosted hydrogen sulfide selective detection and cystathionine γ-lyase activity sensitive evaluation - Zhao Li; Xuan Zhang; Haorong Cheng; Zhongyuan Gu; Changchun He; Ju Wang; Xinxin Shi; Weidan Na; Tongxiang Li; Lin Tian (Chemical Engineering Journal, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Near-infrared light initiated crosslinking via upconversion nanocomposites for spatiotemporally controlled bioconjugation - Qian Hu; Ruotong Li; Sixin Xu; Chunan Cheng; Zhenyu Xing; Yifeng Zhang; Lingkai Meng; Mingdi Yan; Na Kong; Xingjun Zhu (Chemical Engineering Journal, 2024)

Synergistic implementation of efficient adsorption-diffusion-conversion in lithium-sulfur batteries via built-in electric field constructed by transition metal selenides - Jun Wang; Kai Huang; Qi Li; Guo Cheng; Yongzheng Zhang; Na Teng; Cheng Lian; Cheng Ma; Jitong Wang; Wenming Qiao; Licheng Ling (Chemical Engineering Journal, 2024)

Research Advances in Neuroblast Migration in Traumatic Brain Injury - Na Wu; Wenlang Li; Qiang Chen; Meng Chen; Siyuan Chen; Chongjie Cheng; Yimin Xie (Molecular Neurobiology, 2024)
Neuroblasts were first derived from the adult mammalian brains in the 1990s by Reynolds et al. Since then, persistent neurogenesis in the subgranular zone (SGZ) of the hippocampus and subventricular zone (SVZ) has gradually been recognized. To date, reviews on neuroblast migration have largely investigated glial cells and molecular signaling mechanisms, while the relationship between vasculature and cell migration remains a mystery. Thus, this paper underlines the partial biological features of neuroblast migration and unravels the significance and mechanisms of the vasculature in the process to further clarify theoretically the neural repair mechanism after brain injury. Neuroblast migration presents three modes according to the characteristics of cells that act as scaffolds during the migration process: gliophilic migration, neurophilic migration, and vasophilic migration. Many signaling molecules, including brain-derived neurotrophic factor (BDNF), stromal cell-derived factor 1 (SDF-1), vascular endothelial growth factor (VEGF), and angiopoietin-1 (Ang-1), affect vasophilic migration, synergistically regulating the migration of neuroblasts to target areas along blood vessels. However, the precise role of blood vessels in the migration of neuroblasts needs to be further explored. The in-depth study of neuroblast migration will most probably provide theoretical basis and breakthrough for the clinical treatment of brain injury diseases. Graphical Abstract

Ti3C2 quantum dots-modified oxygen-vacancy-rich BiOBr hollow microspheres toward optimized photocatalytic performance - Tao Cheng; Zipeng Xing; Na Zhang; Peng Sun; Hui Peng; Zhenzi Li; Nan Wang; Wei Zhou (Chemosphere, 2024)

The monokaryotic filamentous fungus Ustilago sp. HFJ311 promotes plant growth and reduces Cd accumulation by enhancing Fe transportation and auxin biosynthesis - Shengwang Wang; Xiaofan Na; Meiyun Pu; Yanfang Song; Junjie Li; Kaile Li; Zhenyu Cheng; Xiaoqi He; Chuanji Zhang; Cuifang Liang; Xiaomin Wang; Yurong Bi (Journal of Hazardous Materials, 2024)

Review of reactor systems for hydrogen production via ammonia decomposition - Na Li; Cheng Zhang; Dong Li; Wenbin Jiang; Fojin Zhou (Chemical Engineering Journal, 2024)

New steroidal saponins from the roots of Paris verticillata - Yang Liu; Na Tang; Xiao-Ying Qian; Tian-Yi Li; Qian Zhang; Peng-Cheng Qiu; Hai-Feng Tang; Yun-Yang Lu; Bang-Le Zhang (Natural Product Research, 2024)

Genomic profiling of biosynthetic potentials of medicinal secondary metabolites for ‘Aliisedimentitalea scapharcae’ KCTC 42119T, isolated from ark shell - Jin-Cheng Rong; Lin-Lin Cui; Na Li; Mao-Li Yi; Bo-Tao Huang; Qi Zhao (Marine Genomics, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Effect of inlet velocity on the hydraulic and filtering performance of a Y‐type screen filter - Na Li; Junfeng Li; Liming Yu; Wenhan Yang; Xuelian Liu; Qiao Cheng (Irrigation and Drainage, 2024)
Uneven sediment distribution affected by inlet velocity, particle size distribution and flow field characteristics leads to local clogging in a Y‐type screen filter. This study revealed the detailed flow field characteristics and distribution of sediments on the screen via computational fluid dynamics combined with the discrete element method (CFD–DEM) simulations and experimental tests. The results showed that the distribution of the flow rate on the filter screen was extremely uneven, with the maximum flow rate being 11.72 times greater than the minimum rate. The flow rate was distributed symmetrically on the two sides along the outlet centreline, as shown by the unfolded drawing of the filter core. Numerical simulation and experimental tests using sandy water showed that the number and average particle diameter on the screen decreased, and the number and average particle diameter in the plug increased, with increasing inlet velocity. The sediments on the screen were distributed intensively, and the plugging extent coefficient and the anti‐clogging performance improved. However, this process was more likely to cause local clogging and worsen the filtration performance. Therefore, low‐speed filtering should be applied if the filtering effect is needed, and high‐speed filtering should be applied if the filtering efficiency is favourable but the flushing frequency increases.

Short-term electrochemical stimulation induces sustained enhancement of extracellular pollutant degradation in anaerobic granular sludge - Liang Cheng; Shu-Na Li; Xiang-Tong Zhou; Xiang Xiao; Yang-Yang Yu (Journal of Water Process Engineering, 2024)

Simulated logistical transport effects on textural change of wax apple using different packaging types during storage time - Wanqi Wei; Na Zhang; Baoqing Li; Tong Zhao; Chiyun Cheng; Cunkun Chen; Hao Deng; Ruixiang Yan (Food Packaging and Shelf Life, 2024)

Study on multiple influence mechanism of airflow-dust-gas coupling diffusion under large vortex flow technology - Na Qin; Haiming Yu; Peibei Wang; Xu Li; Xin Qiao; Weimin Cheng (Building and Environment, 2024)

Electroacupuncture Inhibits Neuroinflammation Induced by Astrocytic Necroptosis Through RIP1/MLKL/TLR4 Pathway in a Mouse Model of Spinal Cord Injury - Hongdi Zhao; Xiaoqin Zong; Long Li; Na Li; Chunlei Liu; Wanchao Zhang; Juan Li; Cheng Yang; Siqin Huang (Molecular Neurobiology, 2024)

Sublethal effect and detoxifying metabolism of metaflumizone and indoxacarb on the fall armyworm, Spodoptera frugiperda - Li Zhang; Hui-Zi Wu; Pei-Yun He; Hai-Qun Cao; Wan-Na Zhang; Ying-Chuan Peng; Cheng-Wang Sheng (Pesticide Biochemistry and Physiology, 2024)

Occurrence and distribution of antibiotics and antibiotic resistance genes from the land to ocean in Daliao River-Liaodong Bay, China - Yunfeng Xu; Hui Gao; Ruijing Li; Yingbin Lou; Bing Li; Guanjie Cheng; Guangshui Na (Marine Environmental Research, 2024)

Risk assessment of broflanilide for human and non-target terrestrial organisms in cauliflower production - Hongfang Lin; Yuanping Yang; Na Li; Siyu Liu; Lijing Yang; Yu Cheng; Huishan Sheng; Hui Li; Wanting Wen; Yongze Guo; Yuting Zhang (Environmental Research, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Ce enhanced low-temperature performance of Mn modified Cu-Beta zeolite catalyst for NH3-SCR - Xin Guo; Zhiyong Ding; Na Kang; Liu Yang; Yuanjiang Wang; Cheng Zhang; Zhaoqiang Li; Tiantian Zhang; Yan Wang; Yu Wang; Hao Qu (Fuel, 2024)

Characterization of the broad-spectrum phage vB_CsaM_CBT2 and its inhibition of multidrug-resistant Cronobacter sakazakii in powered infant formula - Bin Cheng; Diwei Zhang; Ting Wang; Hanfang Chen; Yuhang Wang; Yang Wang; Zongyang Li; Na Ling; Yingwang Ye (Food Control, 2024)

Cross-talk between Vimentin and autophagy regulates blood-testis barrier disruption induced by cadmium - Na Chen; Xiaoyan Wan; Mei Wang; Yamin Li; Xiaofei Wang; Ling Zeng; Jinzhao Zhou; Yanwei Zhang; Shun Cheng; Yi Shen (Environmental Pollution, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Are you a happy traveler? Exploring ridesourcing travelers' satisfaction and subjective well-being - Hongyun Si; Na Li; Long Cheng; Guangdong Wu; Jonas De Vos (Transportation Research Part D: Transport and Environment, 2024)

Appropriateness of introducing earthworms into sustainable agriculture from the perspective of soil carbon emissions - Xiangdong Li; Na Mao; Weixin Zhang; Xiaorong Wei; Tong Liu; Jiong Cheng; Ming’an Shao (Soil and Tillage Research, 2024)

Inhibition of quorum sensing serves as an effective strategy to mitigate the risks of human bacterial pathogens in soil - Jinghan Zhang; Kun Lu; Lin Zhu; Na Li; Da Lin; Yangjuan Cheng; Meizhen Wang (Journal of Hazardous Materials, 2024)

Fate of organophosphate esters from the Northwestern Pacific to the Southern Ocean: Occurrence, distribution, and fugacity model simulation - Tengda Shi; Ruijing Li; Jie Fu; Chao Hou; Hui Gao; Guanjie Cheng; Haibo Zhang; Shuaichen Jin; Liang Kong; Guangshui Na (Journal of Environmental Sciences, 2024)

Characterization of emopamil binding protein (Cs-ebp) reveals its potential role in cholesterol biosynthesis and growth performance of Chinese tongue sole - Zhangfan Chen; Xihong Li; Peng Cheng; Jiaqi Mai; Yuqi Sun; Jiacheng Wang; Rui Shi; Qi Zhang; Na Wang; Songlin Chen (Aquaculture, 2024)

Biodegradation of vulcanized natural rubber by enriched bacterial consortia - Yangjian Cheng; Yanchen Wei; Hongliang Wu; Tingting Zhang; Shihua Li; Na Zhu; Qiyun Zhang; Wen Li (Chemical Engineering Journal, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Distribution and migration of heavy metals in the sediment-plant system: Case study of a large-scale constructed wetland for sewage treatment - Rongwei Xiong; Yong Li; Xiufang Gao; Yan Xue; Jinquan Huang; Na Li; Cheng Chen; Ming Chen (Journal of Environmental Management, 2024)

Response of distributions and emissions of summer biogenic sulfur in the Pacific Arctic to enhanced Pacific Water inflow - Cheng‐Xuan Li; Bao‐Dong Wang; Kan Chen; Gui‐Peng Yang; Jian‐Fang Chen; Li‐Na Lin; Zi‐Cheng Wang (Limnology and Oceanography, 2024)
The inflow of warm and nutrient‐rich Pacific Water (PW) through the Bering Strait into the Arctic Ocean is likely to have far‐reaching consequences for the ecosystem and biogenic sulfur cycle in the Earth's sensitive subarctic–arctic region of the Pacific sector, even impacting climate change under global warming scenarios. We performed a detailed biogeochemical study of summer biogenic sulfur cycling from cold (2012) to warm (2014) years in the Bering Strait and the Chukchi Sea, so as to highlight the importance of enhanced Pacific inflow in driving dimethylsulfide (DMS) variability. In the Bering Strait, the enhanced Pacific inflow led to the vertical expansion of the eastern high‐DMS regions due to the vertical extension of Alaska Coastal Water, and the horizontal expansion of the western surface high‐DMS regions due to the westward intrusion of Bering Shelf Water. The enhanced extension of PW potentially stimulated seawater warming, the northward retreat of the ice edge, and the enlargement of sea ice‐free areas in the Chukchi Sea. The northern ice melting zone at 71°N with a bloom of phytoplankton was an area of locally high dimethylsulfoniopropionate concentrations and slow DMS consumption in 2012. A hotspot for dimethylated sulfur compound concentrations and DMS sea–air flux occurred in the convergence region near 67.7°N during 2014, due to enhanced mixing caused by increased Bering Sea Water. Owing to the increased advection of PW during 2012–2014, surface DMS and its emission to the atmosphere increased sharply by threefold in the Chukchi Sea.

Kaempferol and ginsenoside Rg1 ameliorate acute hypobaric hypoxia induced lung injury based on network pharmacology analysis - Na Li; Yuan Cheng; Tao Jin; Lirui Cao; Jieyu Zha; Xiong Zhu; Qing He (Toxicology and Applied Pharmacology, 2023)

Simultaneous extraction of C3H8 and C2H6 from ternary C3H8/C2H6/CH4 mixtures in an ultra-microporous metal–organic framework - Lan Lan; Nan Lu; Jia-Cheng Yin; Qiang Gao; Feifan Lang; Ying-Hui Zhang; Hong-Xiang Nie; Na Li; Xian-He Bu (Chemical Engineering Journal, 2023)

Boosted zn-ion storage in high crystalline VS4 anode by enhanced diffusion-controlled kinetics - Cheng Zheng; Zhu Guo; Bangquan Jian; Zuochao Chen; Jiarui Zhong; Na Li; Shaoming Huang (Chemical Engineering Journal, 2023)

Amino-terminated carbon dots for imaging Golgi apparatus polarity in live cells - Lei Zhan; Peng Hou; Na Chen; Yuan Fang Li; Chun Mei Li; Cheng Zhi Huang (Chemical Engineering Journal, 2023)

Bifunctional polyimide/ZIF8 composite nanofibrous membranes with controllable bilayer structure for bioprotective application and high-efficiency oil/water separation - Meng Chen; Xihui Cheng; Jiwei Li; Na Wang (Journal of Environmental Chemical Engineering, 2023)

Towards the automated virtual trial assembly of large and complex steel members using terrestrial laser scanning and BIM - Jiepeng Liu; Na Cui; Guozhong Cheng; Dongsheng Li; Xiaoxiao Ma; Yue Liao (Engineering Structures, 2023)

Genetic mapping of the wheat leaf rust resistance gene Lr19 and development of translocation lines to break its linkage with yellow pigment - Shoushen Xu; Zhongfan Lyu; Na Zhang; Mingzhu Li; Xinyi Wei; Yuhang Gao; Xinxin Cheng; Wenyang Ge; Xuefeng Li; Yinguang Bao; Zujun Yang; Xin Ma; et al. (Theoretical and Applied Genetics, 2023)

Association between meteorological factors and COVID-19 transmission in low- and middle-income countries: A time-stratified case-crossover study - Yu Wang; Yiran Lyu; Shilu Tong; Cheng Ding; Lan Wei; Mengying Zhai; Kaiqiang Xu; Ruiting Hao; Xiaochen Wang; Na Li; Yueyun Luo; Yonghong Li; et al. (Environmental Research, 2023)

Phthalate exposure with sperm quality among healthy Chinese male adults: The role of sperm cellular function - Pan Yang; Lang-Jing Deng; Jin-Ying Xie; Xiao-Jie Li; Xiao-Na Wang; Bin Sun; Tian-Qing Meng; Cheng-Liang Xiong; Yi-Chao Huang; Yi-Xin Wang; An Pan; Da Chen; et al. (Environmental Pollution, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

Dynamic Measurements of Cerebral Blood Flow Responses to Cortical Spreading Depolarization in the Murine Endovascular Perforation Subarachnoid Hemorrhage Model - Jin Yan; Wenlang Li; Chao Zhou; Na Wu; Xiaomin Yang; Qiuling Pan; Tao He; Yue Wu; Zongduo Guo; Yongzhi Xia; Xiaochuan Sun; Chongjie Cheng (Translational Stroke Research, 2023)

Spatial distribution, source, and ecological risk of polybrominated diphenyl ethers (PBDEs) and hexabromocyclododecanes (HBCDs) in Jiaozhou Bay, China - Jie Fu; Haibo Zhang; Ruijing Li; Tengda Shi; Lisha Wang; Guanjie Cheng; Jiajin Huang; Shisheng Li; Hui Gao; Shuaichen Jin; Guangshui Na (Marine Pollution Bulletin, 2023)

Understanding the public's willingness to participate in the Carbon Generalized System of Preferences (CGSP): An innovative mechanism to drive low-carbon behavior in China - Hongyun Si; Na Li; Xu Duan; Long Cheng; Zhikang Bao (Sustainable Production and Consumption, 2023)

Effects of sericin on oxidative stress and PI3K/AKT/mTOR signal pathway in cryopreserved mice ovarian tissue - Wei Han Shu; Song He Yang; Meng Wei; Xiao Chao Liu; Zi Xuan Chen; Chen Yang Wei; Xin Zhang; Li Na Si; Zhi Hong Chen; Yue Bing Qiao; Dong Mei Li; Tie Cheng Sun; et al. (Cryobiology, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Cobalt nanoparticles induce mitochondrial damage and β-amyloid toxicity via the generation of reactive oxygen species - Jingrong Chen; Cheng Chen; Na Wang; Chunyu Wang; Zhaohui Gong; Jingxian Du; Honglin Lai; Xinpei Lin; Wei Wang; Xiangyu Chang; Michael Aschner; Zhenkun Guo; et al. (NeuroToxicology, 2023)

Construction of hemp seed protein isolate-phosphatidylcholine stablized oleogel-in-water gel system and its effect on structural properties and oxidation stability - Tong Wang; Na Li; Wang Zhang; Yanfei Guo; Dianyu Yu; Jinju Cheng; Liqi Wang (Food Chemistry, 2023)

Magnetic metal–organic frameworks as adsorbents for the detection of azo pigments in food matrices - Lei Cheng; Rong Huang; Qiang Cao; Na Liu; Peiyi Li; Mengmeng Sun; Haiyang Qin; Lidong Wu (Food Chemistry, 2023)

Revealing key meso-particles responsible for irreversible membrane fouling in an integrated oxidation-coagulation ultrafiltration system: Fouling behavior and interfacial interaction mechanism - Guang Yang; Juan Li; Zhiyang Cheng; Qingwen Qin; Hongwei Zhang; Na Lu; Jie Wang (Chemical Engineering Journal, 2023)

Retraction Note: Downregulation of long non-coding RNA TUG1 suppresses tumor growth by promoting ubiquitination of MET in diffuse large B-cell lymphoma - Hai Cheng; Zhiling Yan; Xue Wang; Jiang Cao; Wei Chen; Kunming Qi; Dian Zhou; Jieyun Xia; Na Qi; Zhenyu Li; Kailin Xu (Molecular and Cellular Biochemistry, 2023)

Sensitivity analysis of seismic attributes and oil reservoir predictions based on jointing wells and seismic data – A case study in the Taoerhe Sag, China - Na Li; Jinliang Zhang; Jun Matsushima; Cheng Song; Xuwei Luan; Ming Dou; Tao Chen; Lingling Wang (Frontiers in Marine Science, 2022)
It is important to identify the location of gravelly sandstone in Taoerhe Sag, an oil target area in the Chezhen Depression. To date, most attention has focused on sedimentary characteristics; hence, information regarding a clear sensitivity analysis of seismic attributes is incomplete. To address this, we used well analysis and seismic attribute interpretation to find sensitive seismic attributes and sand bodies. Based on the well analysis and core data, a geologicald model of mudstone and sandstone was established, and the electrical characteristics of three kinds of lithology were identified. We used correlation analysis to select the optimal logging parameters and seismic attributes to identify sandstone. We used multi-attribute fusion technology and stratigraphic slices to characterize the spatial distribution characteristics of gravelly sandstone in the target area and used genetic algorithm inversion volume to evaluate the prediction results. The results indicate that the three main lithologies of the lower submember of Shahejie Formation 3 (P 2 S 3 X ) in the Taoerhe Sag can be distinguished by natural gamma (GR), acoustic time difference (AC) and saturated hydrocarbon content (SH) logging curves. The seismic attribute characteristics of gravelly sandstone of P 2 S 3 X are high root mean square amplitude (RMS) values, high instantaneous bandwidth (BW) values, low 3D curvature (Curv) values, medium-high instantaneous phase (Phase) values and high instantaneous frequency (Freq) values. In this study, we found two nearshore underwater fans in P 2 S 3 X . Gravelly sandstone is located along the slope zone and the lake bottom, with a total sedimentary area of 57.9 km 2 . The method summarized in this paper can be applied to other similar deep-water basins.

Visualizing Seizure Propagation in Freely-moving Mice via Miniature Two-photon Microscopy - Zhuoran Zhang; Shihe Jiang; Kaibin Shi; Yan Li; Wei-Na Jin; Qiang Liu; Ting Zhao; Heping Cheng; Fu-Dong Shi (Neuroscience Bulletin, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Green surfactant-modified TiO2 nanoparticles doped with La-Cr bimetal for NOx removal - Wen Nie; Weiwei Zhou; Na Li; Yun Hua; Qiu Bao; Jiayi Yan; Mingyue Yuan; Cheng Guo; Fengning Yu; Wenjin Niu; Chengyi Liu (Environmental Science and Pollution Research, 2022)

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

Secoiridoid glycosides from the fruits of Cornus officinalis - Xin Wang; Xiang-Jian Zhong; Na Zhou; Lin-Lin Ji; Jin-Jie Li; Ning Cai; Qing-Bo Wang; Peng-Cheng Lin; Xiao-Ya Shang (Natural Product Research, 2022)

Structure and stability analysis of antibacterial substance produced by selenium enriched Bacillus cereus BC1 - Shanxiu Ming; Xujun Chen; Na Zhang; Shuyi Li; Zhenzhou Zhu; Shuiyuan Cheng (Archives of Microbiology, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

MiR-582-3p participates in the regulation of biological behaviors of A549 cells by ambient PM2.5 exposure - Mei Yang; Liangliang Ju; Changlian Li; Han Cheng; Na Li; Qi Zhang; Shu Sun; Liu Ding; Xinmiao Sui; Chao Zhang; Mingwei Yang; Jiyu Cao; et al. (Environmental Science and Pollution Research, 2022)

Decreased incidence of acute hemorrhagic conjunctivitis associated with enhanced public health intervention during the COVID-19 epidemic in China, 2020 - Li Zhang; Xiangyu Guo; Hui Jiang; Na Zhao; Wei Cheng; Wangli Xu; Shelan Liu (Archives of Virology, 2022)

Identification of A-to-I RNA editing profiles and their clinical relevance in lung adenocarcinoma - Cheng Wang; Mingtao Huang; Congcong Chen; Yuancheng Li; Na Qin; Zijian Ma; Jingyi Fan; Linnan Gong; Hui Zeng; Liu Yang; Xianfeng Xu; Jun Zhou; et al. (Science China Life Sciences, 2022)

Promotional effect of ZrO2 and WO3 on bimetallic Pt-Pd diesel oxidation catalyst - Rongrong Fan; Zhaoqiang Li; Yu Wang; Yan Wang; Zhiyong Ding; Cheng Zhang; Na Kang; Xin Guo; Rong Wang (Environmental Science and Pollution Research, 2022)

Correction to: μ-Opioid Receptor–Mediated Enteric Glial Activation Is Involved in Morphine-Induced Constipation - Hui Gao; Yuxin Zhang; Yansong Li; Haiqing Chang; Bo Cheng; Na Li; Wei Yuan; Shuang Li; Qiang Wang (Molecular Neurobiology, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

μ-Opioid Receptor–Mediated Enteric Glial Activation Is Involved in Morphine-Induced Constipation - Hui Gao; Yuxin Zhang; Yansong Li; Haiqing Chang; Bo Cheng; Na Li; Wei Yuan; Shuang Li; Qiang Wang (Molecular Neurobiology, 2021)

Discovery of N-phenyl-1-(phenylsulfonamido)cyclopropane-1-carboxamide analogs as NLRP3 inflammasome inhibitors - Wanwan Li; Zhongqiang Cao; Junjie Cheng; Feiyu Chen; Shuai Li; Yiwei Huang; Long Tai Zheng; Na Ye (Medicinal Chemistry Research, 2021)

Effects of different types of microbial inoculants on available nitrogen and phosphorus, soil microbial community, and wheat growth in high-P soil - Yihui Chen; Shuangshuang Li; Na Liu; Huan He; Xiaoyu Cao; Cheng Lv; Ke Zhang; Jiulan Dai (Environmental Science and Pollution Research, 2021)

Evaluation of the efficacy and safety of hydroxychloroquine in comparison with chloroquine in moderate and severe patients with COVID-19 - Qiuyu Li; Cheng Cui; Fei Xu; Jianping Zhao; Nan Li; Haichao Li; Tianbing Wang; Hua Zhang; Na Liu; Yudong Wei; Xiaoye Niu; Yan Xu; et al. (Science China Life Sciences, 2021)

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

NDRG2 is expressed on enteric glia and altered in conditions of inflammation and oxygen glucose deprivation/reoxygenation - Yuxin Zhang; Hui Gao; Na Li; Haiqing Chang; Bo Cheng; Yansong Li; Jiwen Miao; Shuang Li; Qiang Wang (Journal of Molecular Histology, 2021)

Improving the observation and prediction capabilities for Arctic marine environment: from the perspective of Arctic Shipping - Hui Wang; Qizhen Sun; Lin Zhang; Xi Liang; Qinghua Yang; Na Liu; Chunhua Li; Qingsheng Liu; Bingrui Li; Qian Feng; Xiao Cheng; Yi Yu (Acta Oceanologica Sinica, 2021)

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

A simple anisotropic bounding surface model for saturated clay considering the cyclic degradation - Xinglei Cheng; Na Li; Zhaohuan Yang (European Journal of Environmental and Civil Engineering, 2020)

Cerebral Organoids Repair Ischemic Stroke Brain Injury - Shu-Na Wang; Zhi Wang; Tian-Ying Xu; Ming-He Cheng; Wen-Lin Li; Chao-Yu Miao (Translational Stroke Research, 2020)
Stroke is the second leading cause of death and main cause of disability worldwide, but with few effective therapies. Although stem cell-based therapy has been proposed as an exciting regenerative medicine strategy for brain injury, there are limitations. The developed cerebral organoids (COs) represent a promising transplantation source for stroke that remains to be answered. Here, we transplanted COs at 55 days and explored the feasibility in the rat middle cerebral artery occlusion (MCAO) model of stroke. COs transplantation at 6 h or even 24 h after MCAO significantly reduces brain infarct volume and improves neurological motor function. Transplanted COs show the potential of multilineage differentiation to mimic in vivo cortical development, support motor cortex region-specific reconstruction, form neurotransmitter-related neurons, and achieve synaptic connection with host brain via in situ differentiation and cell replacement in stroke. Cells from transplanted COs show extensive migration into different brain regions along corpus callosum. The mechanisms underlying COs transplantation therapy are also associated with enhanced neurogenesis, synaptic reconstruction, axonal regeneration and angiogenesis, and decreased neural apoptosis with more survival neurons after stroke. Moreover, COs transplantation promotes predominantly exogenous neurogenesis in the transplantation periphery of ipsilateral cortex and predominantly endogenous neurogenesis in the hippocampus and subventricular zone. Together, we demonstrate the efficacy and underlying mechanisms of COs transplantation in stroke. This preliminary but promising study provides first-hand preclinical evidence for COs transplantation as a potential and effective intervention for stroke treatment.

Dryland agricultural environment and sustainable productivity - Gou-Xia Li; Bing-Cheng Xu; Li-Na Yin; Shi-Wen Wang; Sui-Qi Zhang; Lun Shan; Sang-Soo Kwak; Qingbo Ke; Xi-Ping Deng (Plant Biotechnology Reports, 2020)

Transient Receptor Potential Ankyrin 1 Contributes to Lysophosphatidylcholine-Induced Intracellular Calcium Regulation and THP-1-Derived Macrophage Activation - Chao Tian; Rongqi Huang; Feng Tang; Zuoxian Lin; Na Cheng; Xiaobo Han; Shuai Li; Peng Zhou; Sihao Deng; Hualin Huang; Huifang Zhao; Junjie Xu; et al. (The Journal of Membrane Biology, 2020)

RETRACTED ARTICLE: Downregulation of long non-coding RNA TUG1 suppresses tumor growth by promoting ubiquitination of MET in diffuse large B-cell lymphoma - Hai Cheng; Zhiling Yan; Xue Wang; Jiang Cao; Wei Chen; Kunming Qi; Dian Zhou; Jieyun Xia; Na Qi; Zhenyu Li; Kailin Xu (Molecular and Cellular Biochemistry, 2019)

Late Cretaceous magmatism and porphyry Mo–Cu polymetallic mineralization in the Tongchanggou Intrusion, Geza Arc, Southwestern China - Xue-long Liu; Jian-hang Chen; Wen-chang Li; Na Zhang; Shuai-shuai Wang; Chang-zhen Zhang; Ying Luo; Zhen-huan Li; Fu-cheng Yang (Arabian Journal of Geosciences, 2019)

Membrane biofouling retardation by zwitterionic peptide and its impact on the bacterial adhesion - Si-Yu Wang; Deng-Cheng Han; Chao Song; Meng-Na Li; Muhammad Zaheer Afzal; Shu-Guang Wang; Xue-Fei Sun (Environmental Science and Pollution Research, 2019)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Genome-wide identification of SAUR genes in watermelon (Citrullus lanatus) - Na Zhang; Xing Huang; Yaning Bao; Bo Wang; Hongxia Zeng; Weishun Cheng; Mi Tang; Yuhua Li; Jian Ren; Yuhong Sun (Physiology and Molecular Biology of Plants, 2017)

Geochemistry and petrogenesis of Triassic mineralized porphyries in the Geza of the Sanjiang orogenic belt, southwestern China - Xue-long Liu; Wen-chang Li; Na Zhang; Fu-cheng Yang (International Geology Review, 2017)

Post Plasma-Catalysis of Low Concentration VOC Over Alumina-Supported Silver Catalysts in a Surface/Packed-Bed Hybrid Discharge Reactor - Nan Jiang; Cheng Qiu; Lianjie Guo; Kefeng Shang; Na Lu; Jie Li; Yan Wu (Water, Air, & Soil Pollution, 2017)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Relationship between molecular weight, monosaccharide composition and immunobiologic activity of Astragalus polysaccharides - Yiping Jiang; Xiaohui Qi; Kai Gao; Wenjun Liu; Na Li; Ningbo Cheng; Gang Ding; Wenzhe Huang; Zhenzhong Wang; Wei Xiao (Glycoconjugate Journal, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

In vivo activity of vancomycin combined with colistin against multidrug-resistant strains of Acinetobacter baumannii in a Galleria mellonella model - Haifei Yang; Na Lv; Lifen Hu; Yanyan Liu; Jun Cheng; Ying Ye; Jiabin Li (Infectious Diseases, 2016)

Isolation and sequence analysis of the complete NS1 and VP2 genes of canine parvovirus from domestic dogs in 2013 and 2014 in China - Hualei Wang; Hongli Jin; Qian Li; Guoxing Zhao; Nan Cheng; Na Feng; Xuexing Zheng; Jianzhong Wang; Yongkun Zhao; Ling Li; Zengguo Cao; Feihu Yan; et al. (Archives of Virology, 2016)

Responses of carbon transfer, partitioning, and residence time to land use in the plant–soil system of an alpine meadow on the Qinghai-Tibetan Plateau - Liang Zhao; Dongdong Chen; Na Zhao; Qi Li; Qian Cheng; Caiyun Luo; Shixiao Xu; Shiping Wang; Xinquan Zhao (Biology and Fertility of Soils, 2015)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Development of a test strip for rapid detection of lactoperoxidase in raw milk - Hong-xia Che; Bo Tian; Li-na Bai; Li-ming Cheng; Li-li Liu; Xiao-na Zhang; Zhan-mei Jiang; Xiao-xi Xu (Journal of Zhejiang University-SCIENCE B, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Long-term activity of earthquake-induced landslides: A case study from Qionghai Lake Basin, Southwest of China - Xue-li Wei; Ning-sheng Chen; Qian-gong Cheng; Na He; Ming-feng Deng; Javed Iqbal Tanoli (Journal of Mountain Science, 2014)

Synthesis and analgesic evaluation of a series of proline-typed spiro cyclic quaternary ammoniums - Songwen Lin; Na Wang; Shuo Zhao; Qi Sun; Weiwei Zhang; Jia Ye; Tieming Cheng; Runtao Li (Medicinal Chemistry Research, 2014)

Identification of a novel fosfomycin-resistant UDP-N-acetylglucosamine enolpyruvyl transferase (MurA) from a soil metagenome - Gong Cheng; Yongfei Hu; Na Lu; Jing Li; Zhiyun Wang; Quanze Chen; Baoli Zhu (Biotechnology Letters, 2013)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Genome sequence determination and analysis of a Chinese virulent strain, LMS, of Gallid herpesvirus type 2 - Yun Cheng; Feng Cong; Yan-ping Zhang; Zhi-jie Li; Na-na Xu; Guang-yu Hou; Chang-jun Liu (Virus Genes, 2012)

Crucial physical characteristics of sea ice in the Arctic section of 143°–180°W during August and early September 2008 - Ruibo Lei; Zhijun Li; Na Li; Peng Lu; Bin Cheng (Acta Oceanologica Sinica, 2012)

Interaction between iron plaque and root border cells ameliorates aluminum toxicity of Oryza sativa differing in aluminum tolerance - Miao-Zhen Cai; Shu-Na Zhang; Cheng-Hua Xing; Fang-Mei Wang; Lei Zhu; Ning Wang; Li-Yu Lin (Plant and Soil, 2012)

Organ Histopathological Changes and its Function Damage in Mice Following Long-term Exposure to Lanthanides Chloride - Jie Cheng; Na Li; Jingwei Cai; Zhe Cheng; Renping Hu; Qian Zhang; Fangfang Wan; Qingqing Sun; Suxing Gui; Xuezi Sang; Ling Wang; Fashui Hong (Biological Trace Element Research, 2012)

A miR-125b binding site polymorphism in bone morphogenetic protein membrane receptor type IB gene and prostate cancer risk in China - Ninghan Feng; Bin Xu; Jun Tao; Pengchao Li; Gong Cheng; Zhichao Min; Yuanyuan Mi; Meilin Wang; Na Tong; Jialin Tang; Zhengdong Zhang; Hongfei Wu; et al. (Molecular Biology Reports, 2012)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular authentication of geo-authentic Scrophularia ningpoensis - Chuan Chen; Li-na Duan; Xiao-long Zhou; Bing-long Chen; Cheng-xin Fu (Journal of Zhejiang University-SCIENCE B, 2011)

Trace analysis of persistent toxic substances in the main stream of Jiangsu section of the Yangtze River, China - Huan He; Guan-jiu Hu; Cheng Sun; Su-lan Chen; Ming-na Yang; Juan Li; Yong Zhao; Hui Wang (Environmental Science and Pollution Research, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Callus induction and high-efficiency plant regeneration via somatic embryogenesis in Papaver nudicaule L., an ornamental medicinal plant - Jing Li Yang; Bo Zhao; Eun Soo Seong; Myong Jo Kim; Won Hee Kang; Na Young Kim; Chang Yeon Yu; Cheng Hao Li (Plant Biotechnology Reports, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Characterization of the TaAIDFa gene encoding a CRT/DRE-binding factor responsive to drought, high-salt, and cold stress in wheat - Zhao-Shi Xu; Zhi-Yong Ni; Li Liu; Li-Na Nie; Lian-Cheng Li; Ming Chen; You-Zhi Ma (Molecular Genetics and Genomics, 2008)

Construction and characterization of a transformation-competent artificial chromosome (TAC) library ofZizania latifolia (Griseb.) - Fan Na Kong; Shao Mei Jiang; Li Xue Shi; Cheng Li Song; Min De Jin; Shao Lin Jiang; Manli Weng; Bin Wang (Plant Molecular Biology Reporter, 2006)